EFFECTIVENESS OF CTL-BASED STUDENT WORKSHEET IN MEMBRANE TRANSPORT MATTER TO FACILITATE STUDENT’S CRITICAL THINKING ABILITY - Soewondo, Aghniyah; Yuliani, Yuliani (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Abstract The purpose of the research is to know the effectiveness of CTL-based worksheet that facilited the student’s critical thinking ability in membrane transport matter. This research is done by limited trial implementation of valid CTL-based worksheet that developed before and involved 20 students of MIA 2 of Senior High School 2 Kediri on April 2019. Technique of data analysis in this research is descriptive quantitatively. The result of enhancement of student critical thinking ability was shown by improvement of every indicators critical thinking ability after learning by CTL-based worksheet. The pre-test percentage of interpretation, inference, analysis, explanation and evaluation succesively was 62.50%; 57.91%; 57.00%; 51.25% dan 41.25%. Then the post-test percentage was 78.75%; 82.91%; 86.00%; 76.25% dan 63.75%. Besides the percentage of every indicators, the improvement of student’s critical thinking ability was shown by gain score that was 0.53 with middle category. Then efectiveness was based on the student’s postitive responses that reach about 91.60% including the very good category. Keywords : student worksheet, CTL, critical thinking ability, membrane transport